Bushmeat Markets on Bioko Island as a Measure of Hunting Pressure - John E. Fa; Juan E. Garcia Yuste; Ramon Castelo (Conservation Biology, 2000)

Bushmeat Markets on Bioko Island as a Measure of Hunting Pressure - Julia E. Fa; Juan E. Garcia Yuste; Ramon Castelo (Conservation Biology, 2000)
Counts of the number of animal carcasses arriving at Malabo market, Bioko Island, Equatorial Guinea, were made during two, 8‐month study periods in 1991 and 1996. Comparisons of the availability and abundance of individual species between years showed that more species and more carcasses appeared in 1996 than in 1991. In biomass terms, the increase was significantly less, only 12.5%, when compared with almost 60% more carcasses entering the market in 1996. A larger number of carcasses of the smaller‐bodied species (i.e., rodents and the blue duiker [ Cephalophus monticola ] ) were recorded in 1996 than in 1991. Although an additional four species of birds and one squirrel were recorded in 1996, these were less important in terms of their contribution to biomass or carcass numbers. Concurrently, there was a dramatic reduction in the larger‐bodied species, Ogilby's duiker ( C. ogilbyi ) and seven diurnal primates. We examined these changes, especially the drop in the number of larger animals. We considered the possible following explanations: (1) the number of hunters dropped either because of enforced legislation or scarcity of larger prey; (2) a shift in the use of hunting techniques occurred ( from shotguns to snares); or (3) consumer demand for primate and duiker meat dropped, which increased demand for smaller game. Our results suggest that the situation in Bioko may be alarmingly close to a catastrophe in which primate populations of international conservation significance are being hunted to dangerously low numbers. Although there is still a need for surveys of actual densities of prey populations throughout the island, working with the human population on Bioko to find alternatives to bushmeat is an urgent priority.

Diversity and status of sea turtle species in the Gulf of Guinea islands - Javier Castroviejo; Javier Juste B; Jaime Del Val Pérez; Ramon Castelo; Ramon Gil (Biodiversity and Conservation, 1994)

The Spanish co-operation programme in Equatorial Guinea: a ten-year review of research and nature conservation in Bioko - Javier Castroviejo; Javier Justeb; Ramon Castelo; Jaime Del val Pérez (Biodiversity and Conservation, 1994)

Biogeographical considerations of fish diversity in Bioko - Ramon Castelo (Biodiversity and Conservation, 1994)